(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article provides information about the development of contemporary painting in Karakalpakstan. Together with this, the work of the painter S. Baybosinov, who has been creating in Karakalpakstan, is broadly highlighted. Analyses of the works created by the artist are provided. Throughout his career, the artist consistently produces successful works in the style of contemporary painting.